Public Affairs Division at AMR Bank - Mohamed Ariffin, Mohamed Fadzil (1999)
AMR Bank Berhad principal activity was to provide banking services. It started business at a rented three-storey building at Lebuh Ampang, Kuala Lumpur in 1966. In 1997 it became one of Malaysia's largest and most profitable local bank with group net fixed asset reaching RM1.35 billion. By the time it celebrated the silver jubilee anniversary, it was already among the top five financial group, in term of assets, in the country. The bank praised its loyal and committed work force for the invaluable support over the years, along with the Government of Malaysia and the general public, whom all contributed to its success story. The case had highlighted the roles and the challenges faced by the Public Affair Division's (PAD) Director in strengthening the bank's position, especially in facing stiffer competition in the banking industry expected in the near future. While PAD was successful in identifying and implementing its programs, several issues were threatening its operations. The case tried to identify these issues and understands why problems surfaced, and provide suitable solutions to the problems. Several constraints were the factors to the problems occurring at PAD. Firstly, it was not empowered to decide on staff rewards and remuneration, even when it was determined that the reward and remuneration package offered by the bank were below than that offered by other organizations. Secondly, many staffs at PAD were new. Many experienced executives had left the bank in search of better career advancement and remuneration at other organizations. Many were pinched from the division because of their experience in public affairs activities, and the success of AMR Bank's public affairs programs in the eyes of the public. However, the new recruits were lower in productivity and efficiency compared to their predecessors. Coupled with several new programs that were introduced by PAD, the pressure was greatly felt by the Corporate Communication Department, which handled many major programs for the division. Staff workload was high, but sense of urgency to complete one work was low. Staffs' motivations were also reduced due to their lower satisfaction in their pay, benefits, working environment and relationship with fellow employees. Overtime claims were reported to be minimal due to senior executives not interested to stay longer to complete their work. At the request of the parties concerned, all names and characters used in the case have been disguised. It is a mere coincident if names and characters mentioned throughout the case to be the same in anyway with any person or organization.